KAP1 in antiviral immunity: dual roles in viral silencing and immune regulation - Xin, Ruihua; Garigliany, Mutien-Marie; Li, Jianxi (Frontiers in Cellular and Infection Microbiology, 2025)
Krüppel-associated box (KRAB)-associated protein 1 (KAP1), also known as TRIM28 due to its tripartite motif (TRIM) domain, is a member of the transcription intermediary factor 1 (TIF1) family. Since its discovery in 1996, KAP1 has been widely studied as a scaffold protein involved in histone methylation, heterochromatin formation, and genome maintenance. Its function and stability are dynamically regulated by post-translational modifications (PTMs), including phosphorylation, SUMOylation, and acetylation. In addition, KAP1 serves as a signal transducer via its SUMO/ubiquitin E3 ligase activity. This review summarizes current advances in understanding the roles of KAP1 in regulating retroviruses (RVs), herpesviruses, and emerging respiratory viruses such as Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2) and influenza A virus (IAV), with a particular focus on the interplay between its structural domains and physiological functions. Recent findings on human immunodeficiency virus (HIV) are highlighted to address ongoing mechanistic controversies, particularly those involving KAP1-mediated latency control. We further examine novel insights into KAP1’s involvement in other viruses, including hepatitis B virus (HBV), porcine reproductive and respiratory syndrome virus (PRRSV), and African swine fever virus (ASFV). as well as its emerging regulatory roles in host innate immune responses through PTM-mediated modulation of antiviral signaling pathways. Although KAP1 exerts both antiviral and proviral effects, the underlying mechanisms remain incompletely defined, especially in systems where conflicting observations exist for the same pathogen. These discrepancies—reflecting both methodological variation and KAP1’s inherent regulatory complexity—underscore the need for deeper mechanistic insight. Future studies utilizing precise genetic tools and in vivo models will be critical for elucidating the context-specific roles of KAP1 in viral gene regulation and advancing its translational potential.